Portable checkpointing and communication for BSP applications on dynamic heterogeneous grid environments - Camargo, R. Y. de; Kon, F.; Goldman, A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Executing long-running parallel applications in opportunistic grid environments composed of heterogeneous, shared user workstations, is a daunting task. Machines may fail, become inaccessible, or may switch from idle to busy unexpectedly, compromising the execution of applications. A mechanism for fault-tolerance that supports these heterogeneous architectures is an important requirement for such a system. In this paper, we describe the support for fault-tolerant execution of BSP parallel applications on heterogeneous, shared workstations, precompiler instruments application source code to save state periodically into checkpoint files. In case of failure, it is possible to recover the stored state from these files. Generated checkpoints are portable and can be recovered in a machine of different architecture, with data representation conversions being performed at recovery time. The precompiler also modifies BSP parallel applications to allow execution on a grid composed of machines with different architectures. We implemented a monitoring and recovering infrastructure in the InteGrade grid middleware. Experimental results evaluate the overhead incurred and the viability of using this approach in a grid environment.